2001
DOI: 10.1590/s0101-81752001000400013
|View full text |Cite
|
Sign up to set email alerts
|

Espécies do gênero Munida Leach (Crustacea, Decapoda, Galatheidae), distribuídas na costa do Brasil

Abstract: ABSTRACT. Specics of the genus Munida Leach (Crustacea, Decapoda, Gala· theidac) with distribution in lhe Brazilian coast. The purpose of this work is to analyse lhe taxonomy and distributional patterns of the species of the genus Munida Leach, 1820 which occur along lhe Brazilian coast. The species of MUI/ida presenl some peculiar characteristics, rarely found in any other mari ne group . They live in gro ups with great number of individuaIs (gregariou sness) and with several species found together in the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Among these infraorders, the only adult record for Saint Paul's Rocks is from the anomuran Munida sanctipauli Henderson, 1885 (Holthuis et al . ), whose distribution is restricted to the North Atlantic, occurring almost exclusively around islands (Melo‐Filho & Melo ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these infraorders, the only adult record for Saint Paul's Rocks is from the anomuran Munida sanctipauli Henderson, 1885 (Holthuis et al . ), whose distribution is restricted to the North Atlantic, occurring almost exclusively around islands (Melo‐Filho & Melo ).…”
Section: Discussionmentioning
confidence: 99%
“…Larvae of Anomura were also absent around Saint Paul's Rocks, despite their occurrence in the Canary Islands region (Landeira et al 2010). Among these infraorders, the only adult record for Saint Paul's Rocks is from the anomuran Munida sanctipauli Henderson, 1885 (Holthuis et al 1980), whose distribution is restricted to the North Atlantic, occurring almost exclusively around islands (Melo-Filho & Melo 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In our understanding, Canopus is no exception to this fact, which is made even worse when a large number of new species that have been revealed from that location is considered. Since the fauna of Canopus might be at risk due to intense human activities in that area (Melo-Filho & Melo, 2006), it is vital that the local biodiversity is thoroughly investigated so that proper legal protection can be provided. …”
Section: Discussionmentioning
confidence: 99%
“…Global diversity studies of squat lobsters (Schnabel et al 2011b) revealed that the Western Atlantic including the Caribbean, Brazil, and Gulf of Mexico, reported 10.2–12.1% of Chirostyloidea and 10.9–15.4 of Galatheoidea (Campos et al 2005; Fierro et al 2008; Felder et al 2009; Kilgoure and Shirley 2014; de Melo-Filho 2006, de Melo-Filho and de Melo 2001 a, 2001 b; Navas et al 2003; Ortega et al 2014) (Table 1). Nevertheless, the global diversity records of these two groups are incomplete, 19–20% of Chirostylidae and 37–38% of Galatheidae species remain undescribed, particularly in tropical offshore areas (Appeltans et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Squat lobsters (Chirostyloidea and Galatheoidea) are abundant, speciose, and distributed worldwide (Fierro et al 2008; Kilgoure and Shirley 2014; Konishi and Saito 2000; de Melo-Filho 2006; de Melo-Filho and de Melo 1992; de Melo-Filho and de Melo 2001 a and b; Miyake and Baba 1970; Navas et al 2003; Pequegnat and Pequegnat 1970). Schnabel et al (2011a) and Schnabel et al (2011b) recognized ca.1000 species (ca.…”
Section: Introductionmentioning
confidence: 99%